EFEKTIVITAS PENGGUNAAN E-BOOK SEBAGAI MEDIA PEMBELAJARAN DALAM MENINGKATKAN KETERAMPILAN MEMBACA SISWA KELAS XI DI SMA NEGERI 3 LUWU - Revalina Febrianti; Al Narsya Haidar; Nasra Ami Rojuna; Sunatri; Anita Candra Dewi (STKIP Subang, 2026)
This research aims to evaluate the effectiveness of using e-books as a learning medium to improve the reading skills of Grade XI students at SMA Negeri 3 Luwu. The research employed a pre-experimental method with a purposive sampling technique to select a single experimental group. Data were collected through pre-tests, post-tests, and Likert-scale questionnaires covering aspects of ease of use, usefulness, and attractiveness. The results showed a significant increase in the average reading score from 64.20 in the pre-test to 86.50 in the post-test, with classical mastery reaching 94%. Furthermore, the student response analysis yielded an average score of 88%, categorized as